Partycypacja społeczna na rzecz miasta neutralnego klimatycznie - Wasiak, Anna (Public participation in urban climate policy making: The example of Lodz, 2024)
The article presents social participation as a concept that is still new and yet developing very dynamically. In parallel with the development of the approach of cooperation and joint decision-making between local authorities and the local community, there are overlapping processes that have not yet existed in the awareness, and therefore in the debate. Climate threats, reducing greenhouse gas emissions, drought, and weather anomalies are issues so far beyond the sphere of action of local authorities. Cooperation, cooperation and co-decision-making with residents require the development of social and climate participation tools.